Phenotypic, Genetic, and Cytogenetic Evidence of Hybridization Between Species of Trans-Andean Tamarins (Genus Saguinus) (2018)
ABSTRACT: Incomplete reproductive isolation and hybridization is relatively frequent in primates. However, no cases of hybridization between formally recognized species have been reported in tamarins (genus Saguinus), a highly specious group of Neotropical primates. Here, we provide evidence from different sources to demonstrate three cases of hybridization in captivity between species of Saguinus distributed west of the Andes (transAndean). To do this, we described fur color patterns, genotyped 12 microsatellite loci, sequenced the mitochondrial hypervariable region I, and generated chromosomal R bands for the three formally recognized species and the new hybrids of trans-Andean tamarins. We identified one case of interbreeding between the white-footed tamarin (Saguinus leucopus) and the cotton-top tamarin (S. œdipus) and two independent reciprocal crosses of S. leucopus and the Geoffroy’s tamarin (S. geoffroyi). All these hybrids exhibit intermediate phenotypes between parental species, and genetic data are consistent with first- generation hybridization. Cytogenetic data suggest that the S. leucopus × S. œdipus hybrid is sterile, as it is a female with XY karyotype apparently affected by a condition known as gonadal dysgenesis. Trans-Andean tamarin species occur in northwest Colombia with parapatric distributions bounded by major rivers. Potential contact zones, either natural or anthropogenic, might facilitate hybridization in the wild, but this scenario remains to be assessed. Our findings warrant future studies focused on the evolutionary mechanisms of reproductive isolation in tamarins. Given the risk of hybridization, caution should be taken in management and conservation of tamarins.